THE EFFECT OF EDUCATION, TRAINING AND MOTIVATION ON EMPLOYEE PERFORMANCE : A STUDY AT THE RAPPOCINI SUB-DISTRICT OFFICE IN MAKASSAR CITY - Ahmad, Ibrahim; Taufik Tahir; Haeruddin; Mariati; MUhammad Dakhri (Universitas Islam Lamongan, 2024)
This study aims to analyze the influence of education, training, and motivation on employee performance at the Rappocini District Office, by involving 89 employees as a sample. The uniqueness of this study lies in its deep focus on the specific context in the Rappocini District Office, so that the results can provide more relevant insights for management in the government sector. The results of the study show that partially, education has a positive and significant effect on employee performance, where employees with higher education tend to have better performance. Training also has a positive and significant effect, helping employees improve the skills and knowledge needed to carry out their duties. However, motivation shows a negative but significant influence on employee performance, indicating that excessive motivation can lead to pressures that reduce performance. Simultaneously, these three variables have a positive and significant influence on employee performance, demonstrating the importance of a holistic approach in employee development to improve overall performance. The managerial implications of this study emphasize the need to develop structured training programs and better assessment of motivational factors, in order to create a more productive and supportive work environment.